2001
DOI: 10.1002/1522-2683(200107)22:12<2458::aid-elps2458>3.0.co;2-8
|View full text |Cite
|
Sign up to set email alerts
|

Identification of oligomeric domains within dermatan sulfate chains using differential enzymic treatments, derivatization with 2-aminoacridone and capillary electrophoresis

Abstract: Galactosaminoglycans, i.e. dermatan sulfate (DS) and chondroitin sulfate, are linear heteropolysaccharides consisting of repeating disaccharide units of L-iduronic acid (L-IdoA) or D-glucuronic acid (D-GlcA) residues linked to N-acetyl-galactosamine. High-performance capillary electrophoresis (HPCE or CE) has been successfully used for determining the disaccharide composition of glycosaminoglycans. However, only limited information is available on how to identify oligomeric domains rich in D-GlcA or L-IdoA. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
3

Year Published

2002
2002
2011
2011

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 33 publications
0
14
0
3
Order By: Relevance
“…The GAGs separated electrophoretically and transferred onto NC may also be released and recovered from the cationized membranes at the mg-level for further analysis, such as disaccharide pattern evaluation after treatment with specific lyases [35], molecular mass determination [35], characterization of specifically sulfated derivatives or sequences [41,42] inside the polysaccharide chains. According to Karlsson et al [24], the immobilized GAGs are efficiently released from membranes using a nonionic detergent at high ionic strength.…”
Section: Discussionmentioning
confidence: 99%
“…The GAGs separated electrophoretically and transferred onto NC may also be released and recovered from the cationized membranes at the mg-level for further analysis, such as disaccharide pattern evaluation after treatment with specific lyases [35], molecular mass determination [35], characterization of specifically sulfated derivatives or sequences [41,42] inside the polysaccharide chains. According to Karlsson et al [24], the immobilized GAGs are efficiently released from membranes using a nonionic detergent at high ionic strength.…”
Section: Discussionmentioning
confidence: 99%
“…In our laboratory, it has been established the PAGEFS technique for a quick separation of AMAC-derivatized -disaccharide obtained from HA and CS/DS with detection using a CCD-camera [28,39,40]. Capillary electrophoretic (CE) technique has been previously used with success for the separation of AMAC-derivatized -disaccharide obtained from different GAGs [41], as well as for the separation of AMAC-derivatized oligomeric domains obtained from chondroitin sulfate, using both UV detector and LIF detector. This method was optimized and improved by Zinellu et al [42], for the analysis of both HA and CS/DS disaccharides in human plasma.…”
Section: Derivatization Of Gagsmentioning
confidence: 99%
“…In quest for higher sensitivities, current studies have shown that derivatization with AMAC of the HA-and CS/DS-derived -disaccharides and analysis with reversed polarity CZE using a UV detector at 260 nm (absorbance of AMAC), leads to 100-fold increase of sensitivity [41]. A related developed method including similar CZE conditions and AMAC derivatization was used to attempt higher sensitivity for the analysis of all known HE/HS-deriveddisaccharides [43].…”
Section: Analysis Of Gags Disaccharides By Capillary Electrophoresis mentioning
confidence: 99%
See 1 more Smart Citation
“…Quantitative derivatization is generally achieved with 100-fold excess of this reagent. The 2-AMAC molecule has been used for the derivatization of acidic GAGs-derived di-and oligosaccharides and their subsequent HPCE analysis [13,51,75]. The stability of derivatized unsaturated disaccharides has been studied by preparing various mixtures of the standard ∆-disaccharides and keeping them at various temperatures.…”
Section: Fluorophore-assisted Carbohydrate Electrophoresis (Face) Anamentioning
confidence: 99%